2014
DOI: 10.1186/1472-6920-14-50
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between job performance and perceived organizational support in faculty members at Chinese universities: a questionnaire survey

Abstract: BackgroundAlthough several studies have been conducted to investigate the relationship between perceived organizational support (POS) and job performance (JP), it remains unclear whether this relationship is appropriate for faculty members at Chinese universities. The objectives of this study were to (a) examine the correlation between POS andJP; (b) identify the predictors of POS, including demographic and organizational characteristics among faculty members at a Chinese university; (c) investigate the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 53 publications
(85 reference statements)
6
48
1
6
Order By: Relevance
“…8, No. 2;2015(Allen et al, 2013Hui et al, 2007;Miao, 2011). Previous empirical studies support that organizational support was related to job performance.…”
Section: Organizational Supportmentioning
confidence: 60%
“…8, No. 2;2015(Allen et al, 2013Hui et al, 2007;Miao, 2011). Previous empirical studies support that organizational support was related to job performance.…”
Section: Organizational Supportmentioning
confidence: 60%
“…Badania zrealizowane w 2014 roku wśród chińskich pracowników naukowych 19 wykazały również, że na satysfakcję w pracy naukowej wpływały następujące czynniki:…”
Section: Warunki Pracy Naukowejunclassified
“…Intend to leaving the organisation is the possible consequences of a negative atmosphere of the workplace, the lack of perceived organisational support and low organisational commitment (Islam , 2013).In general, it has been found that the employees form a holisticview of the level of organisational support towards themselves and in exchange for this support, the personnel pay attention to organisational goals and achieving them (Baranik 2010;Farid 2015). The staff also responds better to the organisation and do best in order to achieve organisational goals (Gopinathan & Raman, 2015;Guan 2014). By, keeping all such things in mind our aim of this study was to achieve a structural model of the relationship between perceived organisational support and the quality of working life in medical personnel.…”
Section: Research Articlementioning
confidence: 99%